Implementasi Pasal 31 Ayat 2 Huruf C Peraturan Kapolri No. 12 Tahun 2009 Terhadap Penyidikan Penganiayaan Akibat Minuman Keras Di Kepolisian Resor Gorontalo - Swita Grenia Marsyanda; Dian Ekawaty Ismail; Vifi Swarianata (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Implementation of article 31 paragraph 2 letter C of National Police Chief Regulation no. 12 of 2009 regarding the investigation of abuse due to alcohol at the Gorontalo Resort Police. The research used is Empirical Research, which is legal research that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The research results obtained by the author in conducting this research include the application of Article 31 paragraph 2 letter C of the National Police Chief Regulation no. 12 of 2009 at the Gorontalo Resort Police, it has been implemented but is still not able to be implemented optimally because it is seen from the immediate situation and conditions in the field which are not expected. This article has also been effectively implemented in investigations but will be implemented within existing provisions. In investigations, the process is not always handled based on the provisions in these regulations, because investigators carry out the investigation process based on the level of vulnerability and the potential to threaten public safety.